Preclinical Evidence for the Pharmacological Actions of Naringin: A Review - Bharti, Saurabh; Rani, Neha; Krishnamurthy, Bhaskar; Arya, Dharamvir Singh (Planta Medica, 2014)
Naringin, chemically 4′,5,7- trihydroxyflavanone-7-rhamnoglucoside, is a major flavanone glycoside obtained from tomatoes, grapefruits, and many other citrus fruits. It has been experimentally documented to possess numerous biological properties such as antioxidant, anti-inflammatory, and antiapoptotic activities. In vitro and in vivo studies have further established the usefulness of naringin in various preclinical models of atherosclerosis, cardiovascular disorders, diabetes mellitus, neurodegenerative disorders, osteoporosis, and rheumatological disorders. Apart from this, naringin has also exerted chemopreventive and anticancer attributes in various models of oral, breast, colon, liver, lung, and ovarian cancer. This wide spectrum of biological expediency has been documented to be a result of either the upregulation of various cell survival proteins or the inhibition of inflammatory processes, or a combination of both. Due to the scarcity of human studies on naringin, this review focuses on the various established activities of naringin in in vitro and in vivo preclinical models, and its potential therapeutic applications using the available knowledge in the literature. Additionally, it also encompasses the pharmacokinetic properties of naringin and its inhibition of CYP isoenzymes, and the subsequent drug interactions. Moreover, further clinical research is evidently needed to provide significant insights into the mechanisms underlying the effects of naringin in humans.
Keywords: naringin; flavonoid; antioxidant; anti-inflammatory; atherosclerosis; diabetes mellitus; neurological disorders; cardiovascular disorders; hepatoprotection; nephroprotection; bone diseases; gastrointestinal diseases; metabolic syndrome; dentistry; cancer; allergy; drug interaction; pharmacokinetics